Penetapam Flow Cargo di Bandara Soekarno Hatta - Juanda Siahaan (Research and Development Agency of The Ministry of Transportation, 2010)
As a cargo hub airports, at Soekarno Hatta Airport happen every activities of air cargo transport service is very solid, both for domestic and international flights, domestic foreign. For air cargo transport service activities with overseas flight routes, there are two types of service activities that outgoing and incoming cargo export import cargo. Both types of activities are certainly bureaucratic administrative proceess requires that long.As a country that has the potential to increase the capacity of cargo transportation, and has a tremendous opportunity increase economic growth through air freight cargo, then the need for discussion between various parties associated with flow cargo process in Indonesia.